The move to business schools: How is industrial-organizational psychology holding up in Europe? - ANSEEL, Frederik (Institutional Knowledge at Singapore Management University, 2014)
Aguinis, Bradley, and Brodersen (in press) empirically documented the move of Industrial and Organizational (I/O) psychologists to business schools, thereby mainly focusing on the situation in the US. However, in the last decades, I/O psychology has seen a trend towards internationalization. For instance, since the early 90s, there has been a steady increase in the number of authors from outside of the US publishing in Journal of Applied Psychology and Personnel Psychology (Cascio & Aguinis, 2008). Similarly, in international rankings the number of European business schools has increased (Collet & Vives, 2013). This begs the question as to whether a similar move from I/O psychologists to business schools has occurred in Europe as in the US.